PERBANDINGAN DAYA HAMBAT PASTA GIGI ORTODONTIK DENGAN PASTA GIGI NON ORTODONTIK TERHADAP BAKTERI Streptococcus mutans (in vitro) - , DYANING MEITA PARWATI, drg. Sri Suparwitri, S. U., Sp. Ort. (K). ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Teeth were difficult to clean and dental plaque increased due to use of fixed orthodontic appliance. Dental plaque is a microbial deposits on the teeth along with their products, including Streptococcus mutans that cause oral hygiene decreased. Toothpaste is used to maintain oral hygiene. Various toothpastes generally contained different antibacterial agent. Orthodontic toothpaste is used to maintain oral hygiene for fixed orthodontic appliance users . The aim of this study was to know the inhibition differences between orthodontic toothpaste and non orthodontic toothpastes against Streptococcus mutans. The sample consisted of four groups: two groups of orthodontic toothpaste (Enzim® Orthodontic and Fluocaril Orthodontic) and two groups of non orthodontic toothpaste (Enzim® Mint Flavour and Fluocaril Freeze Cool Fresh Breath), each group contained 10 samples. Each group of toothpaste 0,1ml injected into 6 mm diameter wells on Brain Heart Agar media that has been swab Streptococcus mutans. Agar media were incubated at 37oC for 24 hours. Diameter of zone of inhibition were measured using sliding caliper vertically, horizontally, and diagonally and summed then divided by 3. Data were analyzed using one-way ANOVA and LSD0.05. The results showed there was significant statistically differences of zone of inhibition between orthodontic toothpaste and non orthodontic toothpaste brand Enzim® and Fluocaril. LSD0,05 test showed significant differences of inhibition zones between toothpaste groups. The conclusion of this study was orthodontic toothpaste has greater inhibition than non orthodontic toothpaste on the same brand, and Fluocaril orthodontic and non orthodontic toothpaste have greater inhibition than Enzim® orthodontic and non orthodontic toothpaste.